An economic comparison of plastic strawberry plants and exhibition (in sons) In Lattakia - Jableh area - فاروسي عمر; عليو محمود; قدار راما (Latakia University Journal -Biological Sciences Series, 2021)
The aim of this research is to study the economic efficiency of strawberry cultivation by open and protected methods and to make a comparison between the studied cultivation methods and to determine the best ones in terms of economic indicators . Where the study was curried out in 2019 in Jableh region through a questionnaire distributed among 21 farmers who used different methods of cultivating the crop as well as the prices , costs ,and wages for the studied year. The results of the research showed that the total output was about 733200 , 820000 s.p in the andprotected cultivation ponds respectively ,while the profit from the dunum about 330970,317845 s.p ,the profitability coefficient based on costs is reached 104.5 , 110.07 , while the economic efficiency is reached 1.82, 1.63 respectively.The research recommends the necessity to incourage farmers to grow strawberries because it is an economically feasible crop, and work to find ways to support farmers with regard to production requirements, and start extension courses for farmers to direct them towards providing the best services for the strawberry crop